Development of Ultra High Performance Concrete Using Mineral Admixtures and Steel Fibers - Kumar, Piyush (My University, 2015)
Ultra-High Performance Fibre-Reinforced Concrete (UHPFRC) is a relatively new construction material, which is a combination of high performance concrete and fibre reinforcement. The compressive strength reaches beyond 150 MPa, which allows the construction of sustainable and economic buildings with an extraordinarily slim design. In general the aim is to achieve such high strength keeping the cement content under permissible limits. The aim herein is to develop a concrete mix incorporating silica fume, nano silica and ground granulated blast furnace slag (GGBS) with the addition of different percentages of steel fibers, which provides for high performance, durability and better serviceability in addition to overall economy in the long run. In this study, the compressive strength of UHPFRC is studied closely for different percentages of steel fibers with three w/b ratios (0.22, 0.20, and 0.18). The purpose is to have such proportions of materials, including cement replacement materials like silica fume, nana-silica, GGBS etc., which on mixing would be able to provide compressive strengths in the range of 125 to 150 MPa at 28 days. The studies were carried at an early age of 7 days as well. The workability of the different mixtures was constantly maintained by optimum usage of superplasticizers. The results showed that with the increase in the amount of steel fibers the compressive strength of the matrix increased. The maximum strength of UHPFRC, which was achieved under laboratory conditions, was 158 MPa, after 28 days of curing. This strength was achieved for the mix wherein the overall binder content included 8% silica fume, 2% nano silica, 10% GGBS (with remaining 80% as cement content) along with the addition of 1.5% steel fiber. Due to its dense intermolecular locking UHPFRC offers new possibilities in the field where concrete has not been considered viable before. Its high strength can be made use of in the construction of bridge decks, large storage halls, thin walled structures, and columns which can sustain high loading.
M.E. (Structural Engineering)
Keywords: High Performance; fibers; Ultra high performance concrete; Ultra High Performance Fiber Reinforced Concrete; Civil Engineering; CED